Stationary Distribution and Extinction of a Stochastic Microbial Flocculation Model with Regime Switching. (22nd November 2021) - Zhang, Haisu; Song, Yi
Abstract : In this paper, a stochastic microbial flocculation model with regime switching is developed and analyzed. By proposing a suitable stochastic Lyapunov function, the existence and ergodicity of a stationary distribution for the system are proved. Then, the extinction of microorganisms is discussed under appropriate conditions and sufficient conditions for extinction are obtained. Finally, the results of the theoretical analysis are illustrated by numerical simulation.